DESEMPENHO DE VACAS E BEZERROS DE CORTE NO PANTANAL SUPLEMENTADAS COM MISTURA MINERAL UREADA - CASTRO, Micheline Feitosa; HERNANDES, Maria Simara Palermo; SILVA, Andressa Rayane; SILVA, Millena Vitória; VEDOVATTO, Marcelo; OLIVEIRA, Dalton Mendes (ANAIS DO ENIC, 2023)
-